Short Term Neurodevelopmental Outcome of Asphyxiated Term Neonates with Maintenance Phenobarbitone Therapy; Preliminary Findings of Ongoing Study in A Tertiary Care Hospital of Bangladesh (The Journal of Ad-din Women's Medical College, 2023)
Phenobarbitone (PB) is the most commonly prescribed anticonvulsant worldwide to control neonatal seizure in asphyxiated neonates. In spite of limited clinical evidence regarding the best use of drug, their dose and duration: it appears that long term maintenance use of phenobarbitone might slow psychomotor development. Aim of this study was to assess the neuro developmental morbidity in asphyxiated neonates with long term anticonvulsant. This randomized clinical trial enrolled 79 asphyxiated neonates with HIE-II/ III, gestational age ≥ 35 completed weeks from January 2020-January 2021 where cases were categorized into three groups by lottery method. Group A and B received PHB 4mg/kg/day twice daily for 6 weeks and PHB 2mg/kg/day once daily for 2 weeks respectively while Group C didn’t receive any anti-seizure medication. Neurodevelopmental assessment was done at 6 months of age in every case. Data were analyzed by Chi-square & logistic regression test to find out the outcome. Among 79 cases mean gestational age was 37.74±0.98 weeks, M: F was 3:2 and most of them were inborn (51.4%). At 6 months 49 cases were analyzed, 19 were in group A and 15 cases from group B and 15 cases from group C. Cognitive impairment was found 5.844 times more in group A (52.63%) followed by group B (6.67%) and group C (13.33%) (p= 0.001). Group A had 5.844 times more cognitive impairment than other two groups (P= 0.039). No significant functional impairment in motor, speech, hearing and vision were found among the study groups. This study concluded that prolonged use of maintenance Phenobarbitone may impair cognitive function.The Journal of Ad-din Women's Medical College; Vol. 11 (2), July 2023; p 20-25